PELATIHAN AKUNTANSI DASAR SEBAGAI PENDEKATAN DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS PENGURUS KOPERASI SIMPAN PINJAM - Dicky Arisudhana; Sugeng Priyanto; Taqwa Putra Budi Purnomo Sidi Hiram; Indah Rahayu Lestari (CV. Denasya Smart Publisher, 2025)
Savings and loan cooperatives play a vital Impact on enhancing the local economy, with a focus on rural and urban areas that lack adequate access to formal financial services. A major obstacle encountered by these entities is cooperatives is the need to manage their finances efficiently through a well-organized and transparent accounting system. Therefore, community service activities, including basic accounting training for partners, namely the managers of Localized cooperative financial institutions specializing in savings and credit in the neighborhood of cluster area GPE Estate, East Pamulang, are crucial for improving the managers' managerial capabilities, particularly in managing cooperative financial administration using accounting. The training implementation approach was participatory and collaborative, encompassing problem identification, field surveys, preparation of training materials, provision of training on accounting concepts and practices, and monitoring and evaluation activities. The evaluation results of the training activities showed an increase in partners' knowledge and skills in understanding and mastering accounting practices. This was evident in the increase in the average test score of participants, from 59.5 before the training to 79.7 after the training. This increase indicates a significant change in participants' understanding of the material presented. This situation indicates that the training activities have a positive impact on increasing transparency in cooperative financial management. By preparing more transparent and easy-to-understand financial reports, members gain greater trust and are encouraged to actively participate in cooperative management. This increased trust has the potential to reduce the potential for internal conflict and support the sustainability and stability of cooperative operations.